Lithium and its effects on a novel (non drug-induced) hyperactive mouse model - Ostromecki, Alexandra (My University, 2010)
Bipolar disorder (BPD) is a devastating long-term disease for which a significant symptom is mania. Researchers have long relied on the use of rodent models to study psychological disorders (like BPD), as well as to develop pharmaceuticals to treat these diseases. Thus far, however, the most common behavioral proxies of manic symptoms are induced in rodents via treatment with psycho-stimulants. Recently, our lab isolated a line of organically hyperactive mice (L6 mice) that exhibit behavioral characteristics that may be analogous to symptoms of mania (i.e., reduced sleep, increased boldness, increased aggression, and hyperactivity). To test the potential that these animals could be used to model mania, we treated our animals with either standard rodent chow or chow supplemented with the anti-mania drug lithium. We applied various tests commonly used to gauge hyperactivity and other ?mania-like? symptoms in rodents. Tests were run both prior to and post drug treatment to assess lithium?s efficacy in attenuating the ?mania-like? symptoms expressed in the L6 mice, and lithium was in fact found to have an effect in decreasing in-cage hyperactivity. Collectively, this work represents the first step in investigating the possibility that this line of mice could serve as a novel model for mania.
17 p.
Keywords: Zoology; Biology